2016
DOI: 10.1177/0047287516677167
|View full text |Cite
|
Sign up to set email alerts
|

Residents Open Their Homes to Tourists When Disaster Strikes

Abstract: Residents open their homes to tourists when disaster strikes AcknowledgementsWe thank the Australian Research Council (ARC) for support under grants DP110101347 (salary support) and DP120103352 (project support). We thank Tim Coltman and Dominik Ernst for their comments on previous version of this manuscript. AbstractResidents are key stakeholders of tourism destinations. Yet, to date, no study has investigated if and how residents can contribute to destination recovery when a disaster hits. The emergence of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Also, due to the importance of access to the community in predicting visitors' behavioral changes, it would be useful to examine how local communities can support visitors, providing them with the necessary resources, re-shaping their risk perception, and educating them about the most accurate self-protective behaviors. Built upon the support of local communities, how to effectively utilize residents is another important direction in tourism crisis management, especially since research has found that residents can be very useful during the emergency response phase (Hajibaba, Karlsson, & Dolnicar, 2017).…”
Section: Practical Implementationsmentioning
confidence: 99%
“…Also, due to the importance of access to the community in predicting visitors' behavioral changes, it would be useful to examine how local communities can support visitors, providing them with the necessary resources, re-shaping their risk perception, and educating them about the most accurate self-protective behaviors. Built upon the support of local communities, how to effectively utilize residents is another important direction in tourism crisis management, especially since research has found that residents can be very useful during the emergency response phase (Hajibaba, Karlsson, & Dolnicar, 2017).…”
Section: Practical Implementationsmentioning
confidence: 99%
“…In their hypothetical or scenario-based studies, Dolincar and colleagues [53,54] and Hajubaba et al [55] analyzed the issue of the risk-taking in emergency situations. This study also responds to the call by Dolincar and colleagues [53,54], who signified the risk issue in the following statement: "question asking hosts about reasons for refusing permission to buy reveals trust and insufficient information from prospective guests as key drivers of rejection mentioned by 41% of hosts, pointing to hosts undertaking what is effectively a risk-assessment exercise for each booking inquiry" (p. 6).…”
Section: Host's Perspectivementioning
confidence: 99%
“…Empathy has been found as one of the main driver of peer-to-peer communities, inducing supportive reactions even with negative events (Hajibaba, Karlsson and Dolnicar, 2017).…”
Section: Discussionmentioning
confidence: 99%